Retailers as Agents and the Absence of Parallel Trade - Frank Stähler; Keith Maskus (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Legalized parallel trade implies that an original manufacturer cannot control a retailer in a foreign country once the latter has ordered its sales quantity and has compensated the former. This paper endogenizes the role of the retailer as an agent who has private information on the perceived quality of the good in the foreign country. Paradoxically, if parallel trade is permitted there will be no such trade in the only equilibrium, in which the manufacturer offers a smaller volume to the retailer than in the case where it is not permitted. This outcome makes both the original producer and foreign consumers worse off.
Keywords: F13; F15; F12; 330